Pengaruh Aplikasi Vermikompos dan Pupuk Organik Cair Terhadap Pertumbuhan Tanaman Selada Merah (Lactuca Sativa L. Var Crispa) dengan Sistem Budidaya Tanpa Tanah - mohammad pendi; Nurhidayati Nurhidayati; Indiyah Muwarni (AGRONISMA, 2021)
Red lettuce is one of the leaves that has high selling and nutritional value, causing an increase in demand for vegetables. In addition, the development of landless cultivation is also increasing rapidly due to decreasing natural resources due to environmental degradation, such as uncertain climatic conditions, and declining soil fertility. This study aims to determine the effect of the application of vermicompost and liquid organic fertilizer on the growth of red lettuce. This research was conducted in a plastic house on Jl. MT. Haryono, Dinoyo, District Lowokwaru Malang with an altitude of Â± 550 meters above sea level, the air temperature ranges from 20Â o C - 35 oC. This study consisted of 11 treatments consisting of 5 combinations of vermicompost (100, 200, 300, 400, 500 g/pot) with 2 doses of POC (vermiwash and cow urine) and 1 treatment using AB Mix nutrition (control). The results showed that the application of vermicompost and liquid organic fertilizer V2O1 (200 g/pot Vermicompost + Vermiwash) could increase the growth of red lettuce. The application of vermicompost and organic fertilizer was proven to be able to increase the growth of plant height, number of leaves and leaf area of red lettuce compared to the control (AB Mix inorganic fertilizer).